Experimental Study on the Effect of Point Angle on Force and Temperature in Ultrasonically Assisted Bone Drilling - Alam, Khurshid; Ghodsi, Mojtaba; Silberschmidth, Vadim (CMBES Proceedings, 2016)
Drilling of bone is a common surgical procedure in orthopeadics to produce holes for screw insertion. The force and temperature rise in bone drilling are two important factors affecting the outcome of the process. The present work attempts to investigate the effect of drill point angle on the level of force and temperature in bone in the presence of ultrasonic vibrations imposed on the drill along the drilling direction. The effect of ultrasonic frequency and amplitude of vibration on drilling force and temperature was studied using two types of drills with different point angles. The drilling force and temperature were found to be strongly influenced by the drill point angle. The drill with larger point angle caused more force and temperature compared to the drill with smaller point angle. Ultrasonic frequency above 15kHz was observed to produce more temperature in bone for both types of drill geometries. This study found drill with smaller point angle favorable for safe and efficient drilling in the bone.